IV Sodium Ferric Gluconate Complex in Patients With Iron Deficiency Hospitalized due to Acute Heart Failure—Investigator Initiated, Randomized Controlled Trial. Issue 2 (August 2022) - Marcusohn, Erez; Borreda, Itay; Hellman, Yaron; Habib, Manhal; Bahouth, Fadel; Epstein, Danny; Zukermann, Robert
Abstract: Patients with heart failure (HF) with iron deficiency (ID) have worse New York Heart Association class and are at a higher risk of recurrent hospitalizations. Intravenous (IV) iron has been shown to improve exercise ability and reduce hospitalizations. IV sodium ferric gluconate complex (SFGC) has been found to be safe and affordable but has not been studied in this population in a randomized trial. This was a prospective, single-blind, investigator-initiated, randomized controlled trial. Patients admitted for acute heart failure with ID were randomly assigned 1:1 to receive IV SFGC on top of optimal medical treatment. The primary outcome was the change in the 6-minute walk test (6MWT) from baseline to 3 and 6 months. Between September 2019 and May 2021, 34 patients were randomized. 19 patients (55%) were randomized to the treatment arm receiving 125 mg of IV SFGC per day for 3–5 days. COVID-19 was a major barrier to the implementation of the study follow-up protocol, which caused the study to end early. Both groups of patients had similar clinical characteristics, comorbidities, median left ventricular ejection fraction, and rate of death and readmissions due to HF. A higher level of NT-proBNP was observed in patients treated with IV iron (7902 pg/mL vs. 3158, P = 0.04). There was no difference in 6MWT change between groups at 3 months (improvement of 21.6 vs. 24.1 meters) or 6 months (−5 meters vs. 46 meters). In conclusion, IV SFGC–treated patients had a comparable 6-minute walk at 3 and 6 months despite suffering from more severe HF with higher baseline NT-proBNP (NCT04063033).